2020
DOI: 10.1037/xge0000648
|View full text |Cite
|
Sign up to set email alerts
|

United we fall: All-or-none forgetting of complex episodic events.

Abstract: Do complex event representations fragment over time, or are they instead forgotten in an all-or-none manner? For example, if we met a friend in a café and they gave us a present, do we forget the constituent elements of this event (location, person, and object) independently, or would the whole event be forgotten? Research suggests that item-based memories are forgotten in a fragmented manner. However, we do not know how more complex episodic, event-based memories are forgotten. We assessed both retrieval accu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
52
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 96 publications
15
52
8
Order By: Relevance
“…Here, we present the encoding data from our prior work (Cooper and Ritchey, 2019) in which participants encoded and reconstructed complex events. In line with past research (Horner and Burgess, 2013;Joensen et al, 2019), we previously showed that successful recall of event associations in our task -an object with a color, scene location, and sound -exhibits a dependent structure (Cooper and Ritchey, 2019). In the current analyses, we leverage the multimodal aspect of this paradigm to test how features are prioritized and integrated during encoding.…”
supporting
confidence: 54%
“…Here, we present the encoding data from our prior work (Cooper and Ritchey, 2019) in which participants encoded and reconstructed complex events. In line with past research (Horner and Burgess, 2013;Joensen et al, 2019), we previously showed that successful recall of event associations in our task -an object with a color, scene location, and sound -exhibits a dependent structure (Cooper and Ritchey, 2019). In the current analyses, we leverage the multimodal aspect of this paradigm to test how features are prioritized and integrated during encoding.…”
supporting
confidence: 54%
“…However, there was very A key difference between this experiment and previous studies was that we decreased trial timings at both encoding and retrieval. While previous studies have successfully shown memory dependency from separate encoding when participants were given 6 s to encode and retrieve each trial (e.g., Joensen et al, 2020), we allowed only 3 s per encoding and retrieval trial. This difference was implemented to prevent adults performing at ceiling levels in a task otherwise designed to be administered with children, but may have interfered with holistic retrieval in two ways.…”
Section: Experiments 1 Discussionmentioning
confidence: 99%
“…Evidence of pattern completion at retrieval following the encoding of all within-event associations has since been supported by neuroimaging studies, which show that hippocampal activity at retrieval is associated with element-related neocortical activity-even for those event elements not directly tested (Grande et al, 2019;Horner, Bisby, Bush, Lin, & Burgess, 2015). Furthermore, Joensen, Gaskell, and Horner (2020) demonstrated that this retrieval dependency is consistent over time, such that events are likely forgotten in an all-or-none manner.…”
Section: Conditions For Memory Integrationmentioning
confidence: 91%
See 2 more Smart Citations